(untitled) (Research, Society and Development, 2022)
Tomato (Solanum lycopersicum L.) is one of the most important and most cultivated vegetables in the world, having a market for derivative products with high commercial appeal. The inoculation of probiotic bacteria can act in the prevention of diseases such as bacterial spots, bacterial wilt, soft rot, among others, in addition to reducing the use of pesticides and antibiotics, helping to mitigate the impact on humans and environmental health. Part of the samples used for the isolation of LAB was collected from leaves of healthy tomato plants at the Escola de Agronomia (EA) of the Federal University of Goiás (UFG) and another part was obtained from a starter culture from the local market. Two methods of antagonism were used, the diffusion test in a liquid medium and the test in a solid medium. Of the 13 strains tested in this study, 10 showed activity against different phytobacteria, the antagonistic activity test in liquid medium was better compared to a solid medium, broad-spectrum antimicrobial action, and an inhibition halo of up to 22 mm of diameter from a strain obtained from a starter culture. Thus, this work demonstrates the antimicrobial activity of LAB strains tested in vitro against different phytobacteria.